PENGARUH PIJAT TERHADAP INTENSITAS NYERI PASCABEDAH JANTUNG - Sidik Awaludin; Dwi Novitasari (Universitas Harapan Bangsa Purwokerto, 2017)
Pain is the main problem of patient with postoperative cardiac surgery, so it needs to be intervented pharmacological and non-pharmacological therapy. One of non-pharmacological therapy that can be used to treat pain postoperative cardiac surgery is massage. The massage is able to reduce pain through the gate control mechanism and the stimulation of the natural analgesic. The purpose of this study is to identify the influence of massage on pain intensity of postoperative cardiac surgery. The design of this study is quasi-experimental with non-equivalent control group design. The samples in this study were 36 patients with postoperative cardiac surgery. The massage reduced pain intensity significantly through pre and post-treatment (p value <0.05). The massage showed significant effect in reducing postoperative pain scale in cardiac surgery patients. The massage can be used as a part of nursing intervention in reducing postoperative cardiac surgery pain . Keyword: massage; pain; postoperative cardiac surgery